1990
DOI: 10.1128/jb.172.5.2594-2600.1990
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of the Bacteroides fragilis TAL2480 neuraminidase gene, nanH, in Escherichia coli

Abstract: We have cloned the Bacteroides fragilis TAL2480 neuraminidase (NANase) structural gene, nanH, in Escherichia coli. This was accomplished by using the cloning shuttle vector pJST61 and a partial Sau3A library of TAL2480 chromosomal inserts created in E. coli. The library was mobilized into the NANase-deficient B. fragilis TM4000 derivative TC2. NANase-producing colonies were enriched by taking advantage of the inability of TC2, but not the wild-type or NANase+ revertant, to grow in vitro in fluid aspirated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

1991
1991
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 24 publications
1
29
0
2
Order By: Relevance
“…We hypothesized that these genes would be regulated by the presence of NANA in the medium and might share upstream regulatory sequences. Thus, we used the DNA sequences upstream of the nanH gene (25) to search the B. fragilis NCTC 9343 and the unfinished B. fragilis 638R genome databases for matches. Indeed, a matching region was found just upstream of a gene cluster whose protein products showed similarities to proteins involved in NANA catabolism in other organisms.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that these genes would be regulated by the presence of NANA in the medium and might share upstream regulatory sequences. Thus, we used the DNA sequences upstream of the nanH gene (25) to search the B. fragilis NCTC 9343 and the unfinished B. fragilis 638R genome databases for matches. Indeed, a matching region was found just upstream of a gene cluster whose protein products showed similarities to proteins involved in NANA catabolism in other organisms.…”
Section: Resultsmentioning
confidence: 99%
“…This enzyme is found in many pathogenic bacteria and is generally considered a virulence factor (223), and many strains of B. fragilis produce neuraminidase (22,274). Neuraminidase can catalyze the removal of the sialic acid from host cell surfaces and from important immunoactive proteins such as IgG and some components of complement and may consequently disrupt important host functions (237).…”
Section: The Bad Virulencementioning
confidence: 99%
“…pili promoting adherence to epithelial cells and mucus, neuraminidase, and an enterotoxin (Akimoto et al, 1994 ;Brook & Mihal, 1991 ;Brook et al, 1992 ;Duimstra et al, 1991 ;Kleivdal & Hofstad, 1995 ;Moncrief et al, 1995 ;Myers et al, 1989 ;Russo et al, 1990 ;Sack et al, 1992 ;Smith & Callihan, 1992). Previous studies have suggested a role of enterotoxinproducing Bacteroides fragilis (ETBF) in diarrhoeal disease of children (Sack et al, 1994 ;San Joaquin et al, 1995).…”
Section: Abbreviationsmentioning
confidence: 99%